ENHANCING ENGLISH LANGUAGE LEARNING THROUGH INTERACTIVE METHODS - Egambergenova Nurziyo Maxmud qizi (Ustozlar uchun, 2025)
This research investigates interactive classroom techniques that are interactive, such as think-pair-share, debates, and storytelling, and their impact on English language fluency and confidence that are very effective methods for learning English as a second language. This article explains how these methods encourage peer collaboration, spontaneous speech, and real-life language application. The study finds that students who actively engage in meaningful interactions can develop stronger speaking, listening, and comprehension skills. However, it stresses the importance of structuring activities to ensure equal participation. This resource is beneficial for teachers and educators who are aiming to make English lessons more dynamic and student-centered. Furthermore, it addresses the challenges and opportunities associated with integrating technology into English language instruction. By synthesizing current research findings and pedagogical practices, this paper offers insights into optimizing English language teaching in diverse educational contexts.